Meat quality of Argentinean “Camperos” chicken enhanced in omega-3 and omega-9 fatty acids - Azcona, Jorge Oscar; Garcia, Pilar Teresa; Cossu, María Elena; Iglesias, Bernardo Fabricio; Perez, Carolina Daiana; Gallinger, Claudia Isabel; Schang, Marcelo Jorge; Canet, Zulma Edith; Picallo, Alejandra (Elsevier, 2020)
Five diets were assessed with the aim of increasing oleic fatty acid and omega-3 polyunsaturated fatty acid content in ‘campero’ poultry meat and evaluating their influence on sensory attributes. Animals from treatment 1 (T1) were confined and fed with corn/soybean diet; in T2, animals were fed with a corn/soybean mix with free access to pasture; T3 diet had high oleic sunflower seeds (HOSS) and linseeds with access to pasture; T4 diet was similar to T2 with free access to chicory instead of pasture and T5 diet was similar to T3 with free access to chicory instead of pasture. Linseeds and HOSS supplementation significantly increased the fatty acids profile, regardless of forage supply. T3 MUFA content was significantly higher than in the other treatments. Due to the high presence of omega-3 PUFA in linseeds and HOSS treatments (T3 and T5), meat omega-6/omega-3 ratio decreased from 9 to 4. The presence of off-flavours was not influenced by diets but there was an interaction between portion and storage conditions. ‘Poultry meat’ aroma was only influenced by the storage conditions, being slight after 4 months of freezing, while presence of off-aromas was affected by diets. We conclude that it is possible to produce ‘campero’ poultry meat with enhanced omega-3 and omega-9 content and a low omega-6/omega-3 ratio using diets based on linseed and HOSS, without any important change in sensory properties.